2013
DOI: 10.1007/s11135-013-9952-z
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate-based Granger causality between financial deepening and poverty: the case of Pakistan

Abstract: This paper deals with the empirical investigation of causal relationship between financial deepening, economic growth and poverty reduction using quarter frequency data in case of Pakistan over the period of 1972-2011. We applied the ARDL bounds testing approach by incorporating structural breaks stemming in the series. The order of integration of the variables is examined by applying structural break unit root test. Our empirical exercise indicated that long run relationship between financial deepening, econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Ravallion and Datt (2002), Fan et al (2000) and Uddin et al (2014) found that a long-run relationship between financial development, economic growth and poverty reduction exists in Bangladesh, and financial development helps to reduce poverty, but its effect is not linear. Shahbaz and Rehman (2013) find that financial development causes poverty reduction in Pakistan. Shahbaz and Kirkpatrick (2001) tested the relationship between financial development and poverty through the growth channel.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ravallion and Datt (2002), Fan et al (2000) and Uddin et al (2014) found that a long-run relationship between financial development, economic growth and poverty reduction exists in Bangladesh, and financial development helps to reduce poverty, but its effect is not linear. Shahbaz and Rehman (2013) find that financial development causes poverty reduction in Pakistan. Shahbaz and Kirkpatrick (2001) tested the relationship between financial development and poverty through the growth channel.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Household consumption expenditure is measured as a percentage of gross domestic product (GDP). This poverty proxy was used in some studies as a poverty measure (see, Rehman and Shahbaz 2014;Magombeyi and Odhiambo 2017;Kaidi et al 2018;Musakwa and Odhiambo 2020). Household consumption expenditure was selected in the study to capture the income dimen-sion of poverty.…”
Section: Definition Of Variablesmentioning
confidence: 99%
“…Besides that, using the ARDL bounds testing approach, Chani et al (2011) reports that economic growth has a negative and significant impact on poverty in both the long and short run in Pakistan. Cheema and Sial (2012), Rehman and Shahbaz (2014) and Kalim and Hassan (2014) supply evidence that economic growth can significantly reduce poverty levels through financial development. Hence, the findings exemplify the negative relationship between economic growth and poverty, and the rural poor gain more benefits than urban poor individuals: H1.…”
Section: Literature Reviewmentioning
confidence: 99%